1983
DOI: 10.1161/01.str.14.2.246
|View full text |Cite
|
Sign up to set email alerts
|

Auscultation of cervical and ocular bruits in extracranial carotid occlusive disease: a clinical and angiographic study.

Abstract: The clinical and angiographic features of cervical and ocular bruits were correlated in 50 consecutive patients with severe extracranial internal carotid artery occlusive disease. Cervical bruits, generally localized to the carotid bifurcation, were highly associated (P = 0.004) with "tight" (residual lumen less than or equal to 2 mm) internal carotid artery stenosis, but significantly less often with a widely patent or occluded internal carotid artery. Angiographic features of a "slow-flow" state through a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Four patients with ICA occlusion had only ocular bruits, which means, as in a previous report, 10 that ocular bruits are slightly more common than neck bruits in patients with ICA occlusion (4 of 7, 57.1%).…”
Section: + + +supporting
confidence: 81%
See 1 more Smart Citation
“…Four patients with ICA occlusion had only ocular bruits, which means, as in a previous report, 10 that ocular bruits are slightly more common than neck bruits in patients with ICA occlusion (4 of 7, 57.1%).…”
Section: + + +supporting
confidence: 81%
“…Bousser et al 9 found that ocular bruits are seldom related to carotid siphon stenosis, at least as a single cause; in more than half of their patients there was a tight stenosis (24%, 6 of 25) or occlusion (44%, 11 of 25) of the contralateral ICA with bilateral occlusion in one patient. Pessin et al 10 found 76.9% of ocular bruits in their patients contralateral to a tight stenosis (1 of 13) or occlusion (9 of 13) of the ICA. …”
Section: Resultsmentioning
confidence: 84%
“…1 When unilateral diffuse and local¬ ized bruits are considered together, our results show an approximately linear increase in the frequency of carotid bruits as the degree of ipsilat¬ eral carotid stenosis increases, until the artery is occlu.ded, when there is a reduction in the frequency of the bruits (Fig 2). Moderate-to-severe carotid ASO was associated with a carotid bruit in 37% of patients with 50% to 99% stenosis and 33% of A meaningful comparison of the IC and EC carotid ASO grades with the orbital bruit findings was not possi¬ ble, as orbital bruit was detected in only 16 patients. In one case, the arteriogram was normal.…”
Section: Methodsmentioning
confidence: 97%
“…[2][3][4][5] Moreover, ocular bruits have been identified in patients suffering from life-threatening conditions, such as subarachnoid hemorrhage, stroke, and carotid-cavernous fistulas. [6][7][8] Ocular bruit has also been reported as the only auscultatory finding in cases of symptomatic atherothrombotic vascular disease. 9 Despite its clinical relevance, the auscultation of the orbit is often neglected in the routine neurological examination, especially now that better diagnostic tools are replacing clinical examination, 1 including the use of Doppler ultrasound technology in evaluating orbital lesions.…”
Section: Introductionmentioning
confidence: 99%